Pengaruh Gaya Hidup Berbelanja Dan Ketertarikan Fashion Terhadap Pembelian Impulsif Produk Fashion Online Shop : (Survei Pada Mahasiswa Universitas Perjuangan Tasikmalaya Angkatan 2018 Sampai 2021 Yang Pernah Berbelanja Produk Fashion Di Tokopedia) - Aldi Aminudin (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this study was to determine and analyze. The effect Of Shopping Lifstyle and Fashion Involvement In Impulsive Buying Product Fashion Online shop at Tokopedia The research method used in this study is causality research with a survey approach, while the types of data used in this study are primary data and secondary data. The object of this research is the Students From the University Perjuangan Tasikmalaya class off 2018 to 2021who have shopped for fashion products at Tokopedia, with the sampling technique using incidental sampling technique. The data analysis technique used is multiple regression analysis. The results of data analysis show that price perception and product design have a simultaneous and partial influence on Students From the University Perjuangan Tasikmalaya class 2018 to 2021who have shopped for fashion products at Tokopedia